CO2-broadening coefficients for the NO2 transitions at 6.2 µm measured by mid-infrared absorption spectroscopy. (February 2020) - Zhou, Sheng; Yang, Wenbin; Liu, Chengxing; Zhang, Lei; Yu, Benli; Li, Jingsong
Highlight: CO2 -broadening coefficients in the 6.2 µm region have been measured. The continuous wavelet transform is used to determine the number and position of individual peaks. A continuous-wave (CW) mid-infrared quantum cascade laser (QCL)-based spectroscopic sensor is demonstrated. Abstract: A continuous-wave (CW) quantum cascade laser (QCL)-based spectroscopic sensor is demonstrated to investigate the high-resolution spectra of 35 spectral lines of NO2 ranging from 1630.2 cm −1 to 1632.5 cm −1 . The air-broadened half widths of two NO2 lines are compared with the HITRAN database to assess the performance of the system. The absorption spectra of the NO2 and CO2 mixtures at pressures of 10–90 mbar are measured to obtain the CO2 -broadening coefficients. To the best of our knowledge, no measured CO2 -broadening coefficients for the NO2 transitions in this region have been published previously. For signal processing of unresolved lines, a self-established spectral analysis algorithm integrated with the continuous wavelet transform is developed to calculate the second derivative for determining the number and position of individual peaks. The measurement results are useful for the design of a spectroscopic sensor for monitoring carbonated beverages production, tobacco puffing treatment, and food preservation.